Prospective, Randomized Comparison of Intravenous and Oral Ciprofloxacin with Intravenous Ceftazidime in the Treatment of Nosocomial Pneumonia - Raphael Saginur; Gary Garber; Gail Darling; Stephen Shafran; William Cameron; Gwynne Jones; Francois Auclair; the Canadian Infectious Disease Society Multicenter Nosocomial Pneumonia Study Group (Canadian Journal of Infectious Diseases)
OBJECTIVE: To compare the efficacy of intravenous and oral ciprofloxacin and intravenous ceftazidime in the treatment of nosocomial pneumonia.